Antinociceptive, antiallodynic and antihyperalgesic effects of the 5-HT1A receptor selective agonist, NLX-112 in mouse models of pain. (October 2017) - Sałat, Kinga; Kołaczkowski, Marcin; Furgała, Anna; Rojek, Adriana; Śniecikowska, Joanna; Varney, Mark A.; Newman-Tancredi, Adrian
Abstract: Background and purpose: NLX-112 (a.k.a. befiradol, F13640) is a drug candidate intended for the treatment ofl -DOPA-induced dyskinesia. It is a highly selective serotonin 5-HT1A receptor full agonist which has been previously tested in a variety of models of CNS effects including analgesic activity in rat. Its activity in mouse models of pain has not been previously investigated. Experimental approach: The activity of NLX-112 was tested in mouse models of acute pain (hot plate), tonic pain (intraplantar formalin test), in the oxaliplatin-induced neuropathic pain model of chemotherapy-induced peripheral neuropathy and in the streptozotocin (STZ)-induced model of painful diabetic neuropathy. Key results: The main findings indicate that (i) NLX-112 was markedly active in the formalin test with potent reduction of paw licking in both phases of the test (minimal effective dose (MED) 0.5 mg/kg i.p. and p.o. in acute phase, and 0.1 mg/kg i.p. and 1 mg/kg p.o. in late phase). The effects of NLX-112 in this test were completely abolished by the selective 5-HT1A receptor antagonist, WAY100635; (ii) NLX-112 was active in the hot plate test and in the oxaliplatin-induced neuropathic pain model of chemotherapy-induced peripheral neuropathy, but at markedly higher doses (MED 2.5 mg/kg i.p.); (iii) NLX-112 was least active in the STZ-induced model of painful diabetic neuropathy (MED 5 mg/kg i.p.); (iv) NLX-112 did not affect locomotor activity. Conclusions and implications: NLX-112 may have significant potential for treatment of tonic pain but may be less promising as a candidate for treatment of chemotherapy-induced or diabetic neuropathic pain. Graphical abstract: Highlights: NLX-112 is a highly selective serotonin 5-HT1A receptor full agonist. NLX-112 potently reduces paw licking in the early and late phases of the intraplantar formalin test. At higher doses it is active in the thermally-induced acute and oxaliplatin-induced neuropathic pain models. NLX-112 is least active in the diabetic neuropathic pain model. At the highest analgesic dose tested NLX-112 does not affect locomotor activity.